High-sensitivity and spatial resolution transient magnetic and electric field probes for transcranial magnetic stimulator characterizations. Issue 5 (3rd September 2018) - Meng, Qinglei; Daugherty, Michael; Patel, Prashil; Trivedi, Sudhir; Du, Xiaoming; Hong, Elliot; Choa, Fow-Sen
ABSTRACT: Transcranial magnetic stimulation (TMS) is widely used for noninvasive brain stimulation. However, existing TMS tools cannot deliver targeted neural stimulation to deep brain regions, even though many important neurological disorders originate from there. To design TMS tools capable of delivering deep and focused stimulation, we have developed both electric and magnetic field probes to evaluate and improve new designs and calibrate products. Previous works related to magnetic field measurement had no detailed description of probe design or optimization. In this work, we demonstrated a magnetic field probe made of a cylindrical inductor and an electrical field probe modified from Rogowski coil structure. Both have much smaller size and higher directivity than commercial dipole probes. Using probe, we can calibrate and monitor any new types of TMS coil or array design and verify measured results with the other probe. We mathematically analyze their characteristics and performance and obtained a two-dimensional vector plot of the induced electric field, which matched the measured results from the second type of probe. A commercial circular coil and a figure-8 coil, with relatively complex vector field distribution, were used as examples to demonstrate the high-resolution and accurate measurement capability of our probes.